2021
DOI: 10.3390/cells11010109
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics of Idiopathic Inflammatory Myopathies in Juvenile Patients

Abstract: Background: In juvenile idiopathic inflammatory myopathies (IIMs), morphological characteristic features of distinct subgroups are not well defined. New treatment strategies require a precise diagnosis of the subgroups in IIM, and, therefore, knowledge about the pathomorphology of juvenile IIMs is warranted. Methods: Muscle biopsies from 15 patients (median age 8 (range 3–17) years, 73% female) with IIM and seven controls were analyzed by standard methods, immunohistochemistry, and transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
(105 reference statements)
2
3
0
4
Order By: Relevance
“…Although this observation requires further investigation on larger groups of patients, the use of MHC-II immunostaining could be of great value for adult DM patients, as it could represent a new tool, easily usable in routine, to detect a paraneoplastic process. Regarding juvenile cases, in line with the present results, a recent study by Schänzer et al identified a positive MHC-II myofiber immunostaining in 7 out of 9 cases of juvenile DM, with a mild intensity and a scattered distribution, except for 2 cases which showed a perifascicular pattern [46]. Another study, in 2009, found MHC-II positive myofiber immunostaining in only 28% of juvenile DM muscles [45].…”
Section: Myofiber Mhc-ii Immunostaining a Tool For The Diagnosis Of I...supporting
confidence: 90%
See 1 more Smart Citation
“…Although this observation requires further investigation on larger groups of patients, the use of MHC-II immunostaining could be of great value for adult DM patients, as it could represent a new tool, easily usable in routine, to detect a paraneoplastic process. Regarding juvenile cases, in line with the present results, a recent study by Schänzer et al identified a positive MHC-II myofiber immunostaining in 7 out of 9 cases of juvenile DM, with a mild intensity and a scattered distribution, except for 2 cases which showed a perifascicular pattern [46]. Another study, in 2009, found MHC-II positive myofiber immunostaining in only 28% of juvenile DM muscles [45].…”
Section: Myofiber Mhc-ii Immunostaining a Tool For The Diagnosis Of I...supporting
confidence: 90%
“…Indeed, most previous studies were performed several decades ago, impeding the comparison with the currently used classification of IIM subgroups. Although few recent studies report interesting results, each of them analyzed only a particular subgroup [1, 4, 46], thus impeding the identification of MHC-II myofiber immunostaining variation between IIM subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is based on myopathological and immune features including the presence of MHC-I and MHC-II on myofibers [ 51 , 54 ]. MHC class I expression is evidenced on myofibers, showing an intriguing perifascicular pattern different from DM or IMNM patients [ 8 , 63 , 68 ]. MHC class I overexpression is further corroborated by changes to the muscle proteome of ASyS as compared to NDC.…”
Section: Discussionmentioning
confidence: 99%
“…В настоящей работе антинуклеарный фактор в группе пациентов с ЮДМ выявлялся значимо реже, что представляется вполне закономерным и подтверждается данными других исследований [14]. Частота обнаружения миозит-ас-социированных аутоантител у наших больных с ЮИВМ была относительно невысока (10,8%).…”
Section: пациентыunclassified
“…Несмотря на отсутствие повышения содержания ферментов, все эти пациенты имели клинические проявления миопатического синдрома и подтверждение поражения мышц по данным игольчатой ЭНМГ либо визуализирующих методов.В настоящей работе дисфагия значимо реже наблюдалась при ОМ, чем при ЮДМ, а частота выявления клинических признаков дисфагии была несколько выше, чем в других исследованиях, в которых этот показатель составлял от 14,6 до 32%[9, 12,13].Изменения кожи у наших пациентов в целом схожи с описанными в литературе[9, 12,13]. Миопатический тип нарушений при капилляроскопии ногтевого ложа встречался у большинства пациентов, чаще в группе ЮДМ, тогда как, по данным других авторов, частота подобных изменений колеблется в очень широком диапазоне -от 7 до 81%[12,14]. Вероятно, это связано с разными воз-О Р И Г И Н А Л Ь Н Ы Е И С С Л Е Д О В А Н И Я / O R I G I N A L I N V ES T I G A T I O N S Современная ревматология.…”
unclassified